Pemanfaatan Oil Sludge Sebagai Alternatif Pengganti Sebagian Aspal Terhadap Nilai Durabilitas HRS-WC Modifikasi Rendaman Marshall - Zal, Ismi Harry; Malik, Alfian; Sebayang, Mardani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
One of the wastes produced by the petroleum industries is oil sludge. Therefore the handling of oil sludge by utilizing it as a partial substitute for asphalt in a pavement mixture is an effort to reduce the buildup. Road pavements in Indonesia often damaged before its pavement servise life ended because the roads usually submerged by water flood at the rainy seasons. The research aims to determine durability level on HRS-WC mixtures by using oil sludge due to the influence of soaking time. Variations of oil sludge used were 0%, 2%, 4%, 6% and 8% of optimum weight asphalt content in the mixture. Tests were performed using the Marshall test specification of Bina Marga 2010 with modification of immersion duration, i.e. 24 hours, 96 hours, and 168 hours of immersion in the bath with the temperature of 60 ºC. Based on the result of the research, the influence of long soaking influential adequate significant on the durability a mixture of HRS-WC with using oil sludge as a partial substitute for asphalt. The lenght of immersion that meets the specification with minimum retained strenght value 90% for almost all variations of oil sludge content is 96 hours immerson. Maximum oil sludge content that meets the specification for 96 hours immersion is 6% with value of retained strenght 90.64%, first durability indeks 0.37% and second durabiity indeks 8.90%.Keywords: Oil sludge, HRS-WC, Bina Marga Specification 2010 Revision 3, durability